Bioaccumulation and effects of dietary exposure to the alternative flame retardant, bis(2‐ethylhexyl) tetrabromophthalate (TBPH), in the Atlantic killifish, Fundulus heteroclitus. (16th July 2018) - Nacci, Diane; Clark, Bryan; La Guardia, Mark J.; Miller, Ken; Champlin, Denise; Kirby, Ian; Bertrand, Ashley; Jayaraman, Saro
Abstract: Bis(2‐ethylhexyl) tetrabromophthalate (TBPH), a high production volume flame retardant chemical used as a replacement for banned flame retardants, has been detected in media and human and wildlife tissues globally. We describe bioaccumulation and biological effects from dietary exposure of TBPH to an estuarine fish, Atlantic killifish, Fundulus heteroclitus . Briefly, adult fish were fed carrier control or chemically amended diets for 28 d, followed by 14 d of control diet feeding. Diets were amended with TBPH (TBPH_LO diet, 139 μg/g dry wt, or TBPH_HI diet, 4360 μg/g dry wt) or a polychlorinated biphenyl congener (PCB153 diet, 13 μg/g dry wt), which was included as a positive control for bioaccumulation. Although bioaccumulation of either chemical correlated with fish size, only a small proportion of the TBPH offered (<0.5% total TBPH) had bioaccumulated into TBPH‐treated fish by 28 d. In contrast, 24.5% of the PCB153 offered was accounted for in 28‐d PCB‐treated fish. Although 28‐d bioaccumulated concentrations of TBPH differed by sex and treatment, sexes did not differ in their rates of TBPH bioaccumulation, and the time to achieve 50% of 28 d concentration (T1/2 ) was estimated to be 13 d. Depuration rates of TBPH did not differ by sex or treatment, and the time after exposure to achieve T1/2 was estimated to be 22 d. Independent of treatment, male fish grew faster than female fish, but for both sexes reproductive condition (gonadal somatic index) declined unexpectedly over the experimental period. Across treatments, only the TBPH_LO treatment affected growth, reducing male but increasing female growth rates by small amounts relative to respective controls. In summary, our study used very high concentrations of dietary TBPH to contaminate fish tissues above the highest levels reported to date in wild biota, yet we observed few adverse biological effects. Environ Toxicol Chem 2018;37:2350–2360. © 2018 SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.